Kualitas Kebersihan Kamar Tamu di Hotel XXX - Ni Kadek Sri Wahyuni; Ni Ketut Iswarini; Putu Gede Eka Darmaputra (Journal of Hospitality Accommodation Management (JHAM), 2023)
This research is motivated by problems that occur in the hotel industry regarding the cleanliness of guest rooms. Guests hope that the room they get is clean, but in reality what happens is that the room still contains insects and dust. This study aims to find out how the quality of guest room cleanliness at Hotel XXX. Data obtained through data collection techniques of observation, interviews, and documentation. From the results of the interviews, it was found that the cleanliness standards of guest rooms have been set by the hotel. The results of the interviews are used as a reference in making observations. This research approach uses descriptive qualitative data analysis techniques. Research findings show that 67.51% of room hygiene quality is in accordance with established standards.